F-Element silicon and heavy tetrel chemistry. Issue 40 (30th September 2020) - Réant, Benjamin L. L.; Liddle, Stephen T.; Mills, David P.
Abstract : In this perspective we review the molecular chemistry of f-element silicon and heavy tetrel complexes. Abstract : The last three decades have seen a significant increase in the number of reports of f-element carbon chemistry, whilst the f-element chemistry of silicon, germanium, tin, and lead remain underdeveloped in comparison. Here, in this perspective we review complexes that contain chemical bonds between f-elements and silicon or the heavier tetrels since the birth of this field in 1985 to present day, with the intention of inspiring researchers to contribute to its development and explore the opportunities that it presents. For the purposes of this perspective, f-elements include lanthanides, actinides and group 3 metals. We focus on complexes that have been structurally authenticated by single-crystal X-ray diffraction, and horizon-scan for future opportunities and targets in the area.